2020
DOI: 10.21595/vp.2020.21311
|View full text |Cite
|
Sign up to set email alerts
|

Stress analysis of plate with opposite semicircular notches and adhesively bonded piezoelectric actuators

Abstract: Stress control of structures by means of active smart material has evolved in recent years. The structure's stress control can typically be considered as strengthening that effects the structure's load-carrying capability. The stress-concentration cause by holes and notches produces a large variation and significant increase in stress. The control of the stress concentration and its distributions in the notched area is valuable for many practical and design applications. This study investigates the impacts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In the year 2017, a few studies were found on the active repair of metallic structures. For instance, Abuzaid et al ,,, used PZT patches for the repair of the plate through an experimental, numerical, and analytical method since it can be developed for metallic and nonmetallic materials of repair. However, in the next level of study, it can be possible to consider tubes/pipes or other types of structures for active repair because this type of structural repair has been found in passive repair .…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…In the year 2017, a few studies were found on the active repair of metallic structures. For instance, Abuzaid et al ,,, used PZT patches for the repair of the plate through an experimental, numerical, and analytical method since it can be developed for metallic and nonmetallic materials of repair. However, in the next level of study, it can be possible to consider tubes/pipes or other types of structures for active repair because this type of structural repair has been found in passive repair .…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…The influence of different hole patterns and crack locations, obtained as a result of the experiment under cyclic loading, was presented from the experimental samples modeled by the finite element method in ABAQUS. Abuzaid et al [27] studied the concentration and distribution of stresses in notched areas in piezoelectric actuators for an aluminum plate with opposite semicircular notches using the finite element method for external static loading.…”
Section: Introductionmentioning
confidence: 99%